Synthesis, Spectral Characterization and Antioxidant Evaluation of Fluorinated Phenothiazines - Gautam, Naveen; Sharma, Meenakshi; Gautam, Vibha; Sharma, M.K.; Gautam, D.C. (Asian Journal of Chemistry, 2010)
10H-phenothiazines are prepared by Smiles rearrangement. These synthesized compounds have been screened for their antioxidant activity. The structures of 10H-phenothiazines have been established by elemental analysis, IR, 1H NMR and mass spectral data.